Training Program Design Model for Improving PAI Teacher Competency - Mahfida Inayati; Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2024)
The agent of change in the field of education is a teacher who needs a skill and also extensive knowledge to transfer knowledge to students in an effort to improve competence including teachers of Islamic religious education. So it is very important to hone competence and something that becomes new with the development of the times towards teacher competence more – more for Islamic Religious Education teachers. The purpose of designing this training model is to produce a valid training model to improve the competence of Islamic Religious Education teachers so that the author can describe various kinds of training design models for the competence of Islamic Religious Education teachers at the primary, middle and upper levels. The results of the discussion include the concept of designing education and training programs, Design Stages Through Training Models and training design models in improving the competence of PAI teachers such as the IDI, Dick & Carey, Kemp and goad models. The application of the Dick & Carey model in improving the competence of PAI teachers includes significant stages in a training program design.